Comparative Susceptibility of Staphylococcus aureus and S. pyogenes to Musa paradisiaca Linn Leaf Extract and Fusidic Acid in Impetigo Patients - Inda Astri Aryani; Maretha Winny Astria; Rina Novriani; Aulia Rosa Amelinda (Biomedical Journal of Indonesia, 2026)
Introduction. An estimated 12% of the world’s population is at risk of experiencing impetigo. The prevalence of impetigo in developing countries ranges from 111 to 140 million cases. Impetigo often occurs in children aged 2-5 years. One way to overcome this condition involves using natural products or phytochemicals that are effective, safe, and economical. One of the Indonesian plants that can be used as an alternative medicine with antibacterial effects is the kepok banana leaves (Musa paradisiaca Linn). This study aimed to assess the susceptibility of S. aureus and S. pyogenes to the antimicrobial potential of the extract of M. paradisiaca leaf extract and fusidic acid using isolates from impetigo patients. Methods. This in vitro experimental study used a post-test-only control-group design. Bacterial isolates were obtained from impetigo patients and tested using the disk diffusion method following CLSI standards. Group comparisons were conducted using the Kruskal–Wallis test followed by Mann–Whitney U tests. A p-value < 0.05 was considered statistically significant. Results. Bivariate analysis showed a significant difference in the susceptibility of S. aureus between fusidic acid and M. paradisiaca extract (p < 0.05), where fusidic acid demonstrated larger inhibition zones. Similarly, a significant difference was observed for S. pyogenes (p < 0.05). However, there was no significant difference between the 50% and 100% extract concentrations. Conclusion. M. paradisiaca leaf extract exhibits antibacterial activity against S. aureus and S. pyogenes, but is significantly less effective than standard fusidic acid treatment in vitro.